2014
DOI: 10.1097/mlr.0b013e318268ac86
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With Severe Sepsis Using Administrative Claims

Abstract: Background Severe sepsis is a common and costly problem. Although consistently defined clinically by consensus conference since 1991, there have been several different implementations of the severe sepsis definition using ICD-9-CM codes for research. We conducted a single center, patient-level validation of one common implementation of the severe sepsis definition, the so-called “Angus” implementation. Methods Administrative claims for all hospitalizations for patients initially admitted to general medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
156
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 305 publications
(167 citation statements)
references
References 35 publications
7
156
1
Order By: Relevance
“…First, we used claims based algorithms to identify our cohorts. The method for identifying sepsis is commonly used and has similar specificity and greater sensitivity to other claims based methods 19. For the non-sepsis infection and sterile inflammation cohorts, we required a principal diagnosis of infection and sterile inflammatory condition, respectively, to increase the specificity of these cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we used claims based algorithms to identify our cohorts. The method for identifying sepsis is commonly used and has similar specificity and greater sensitivity to other claims based methods 19. For the non-sepsis infection and sterile inflammation cohorts, we required a principal diagnosis of infection and sterile inflammatory condition, respectively, to increase the specificity of these cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Following the procedure of Angus and colleagues, we defined admissions with sepsis by synchronous ICD-9 (international classification of diseases, ninth revision) CM codes for infection and acute organ dysfunction, or explicit coding of severe sepsis or septic shock1 19 (see table A in appendix 5). This reflects the third international consensus definition that sepsis is “life-threatening organ dysfunction caused by a dysregulated host response to infection”20 or what the previous sepsis definition conceptualized as “severe sepsis.”14 We did not require explicit sepsis codes because they were not introduced until 2002, after the start of our study.…”
Section: Methodsmentioning
confidence: 99%
“…These data represent approximately 20% of hospitalized patients in nonfederal US hospitals. 12 Patients with sepsis present on admission were selected through use of International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD-9-CM ) codes for sepsis (038.x) with high positive predictive value (>90%) 13 combined with receipt of an antibiotic. Atrial fibrillation was identified via ICD-9-CM code 427.31 (positive predictive value, 70%-96%; median, 89%) 14 and patients with AF were subclassified as having preexisting AF (eg, diagnosed prevalent AF that was present on admission) or newly diagnosed AF (eg, incident AF that was not present on admission).…”
Section: Methodsmentioning
confidence: 99%
“…We performed an analysis limited to severe sepsis cases identified through a more sensitive, but less specific, algorithm for severe sepsis developed by Angus and colleagues (22) that identifies severe sepsis through concomitant infection and acute organ dysfunction codes (positive predictive value, 70%) and performed a separate analysis limited to the less sensitive and more specific explicit ICD-9-CM codes for severe sepsis (995.92, 785.52, positive predictive value z100%) (23,24).…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 99%